Effect of Croatian propolis on diabetic nephropathy and liver toxicity in mice - Oršolić Nada; Sirovina Damir; Končić Marijana Zovko; Lacković Gordana; Gregorović Gordana (BMC, 2012)
Abstract Background In the present study, we examined the antioxidant effect of water soluble derivative of propolis (WSDP) and ethanolic (EEP) extract of propolis on renal and liver function in alloxan-induced diabetic mice. In addition, we examined whether different extract of propolis could prevent diabetic nephropathy and liver toxicity by inhibiting lipid peroxidation in vivo. Methods Diabetes was induced in Swiss albino mice with a single intravenous injection of alloxan (75 mg kg-1). Two days after alloxan injection, propolis preparations (50 mg kg-1 per day) were given intraperitoneally for 7 days in diabetic mice. Survival analysis and body weights as well as hematological and biochemical parameters were measured. The renal and liver oxidative stress marker malonaldehyde levels and histopathological changes were monitored in the liver and kidney of treated and control mice. Results Administration of propolis to diabetic mice resulted in a significant increase of body weight, haematological and immunological parameters of blood as well as 100% survival of diabetic mice. Alloxan-injected mice showed a marked increase in oxidative stress in liver and kidney homogenate, as determined by lipid peroxidation. Histopathological observation of the liver sections of alloxan-induced diabetic mice showed several lesions including cellular vacuolization, cytoplasmic eosinophilia and lymphocyte infiltrations, but with individual variability.Treatment of diabetic mice with propolis extracts results in decreased number of vacuolized cells and degree of vacuolization; propolis treatment improve the impairment of fatty acid metabolism in diabetes. Renal histology showed corpuscular, tubular and interstitial changes in alloxan-induced diabetic mice. Test components did not improve renal histopathology in diabetic mice. Conclusions Propolis preparations are able to attenuate diabetic hepatorenal damage, probably through its anti-oxidative action and its detoxification proccess as well as the potential to minimize the deleterious effects of free radicals on tissue. The protective role of propolis against the ROS induced damages in diabetic mice gives a hope that they may have similar protective action in humans.